Cointegration in Panel Data with Structural Breaks and Cross‐Section Dependence. (7th October 2013) - Banerjee, Anindya; Carrion‐i‐Silvestre, Josep Lluís
Summary The power of standard panel cointegration statistics may be affected by misspecification errors if structural breaks in the parameters generating the process are not considered. In addition, the presence of cross‐section dependence among the panel units can distort the empirical size of the statistics. We therefore design a testing procedure that allows for both structural breaks and cross‐section dependence when testing the null hypothesis of no cointegration. The paper proposes test statistics that can be used when one or both features are present. We illustrate our proposal by analysing the pass‐through of import prices on a sample of European countries. Copyright © 2013 John Wiley & Sons, Ltd.